Stability of co‐composted hydrochar and biochar under field conditions in a temperate soil. (4th March 2015) - Busch, D.; Glaser, B.; Goss, Michael
Abstract Hydrothermally converted biomass (hydrochar) is evaluated as a carbon‐rich soil amendment in addition to pyrogenic biochar. After assessing the suitability of hydrochar for use in agriculture, its environmental safety and comparing its chemistry with that of biochar, we describe a field trial established at Halle (Germany) under natural conditions for a temperate climate and without further external management practices. The main objective of our study was to analyse the stability and hence the C sequestration potential of composted chars over a period of 2 years. Four treatments (no amendment control, compost, co‐composted hydrochar and co‐composted biochar) in fourfold field replication were chosen to make a direct comparison of biochar and hydrochar under field conditions. The total organic carbon and total N increased in all treatments in comparison with the control but only in biochar‐amended treatments were N concentrations more stable. Composted biochar showed significantly more black carbon content in topsoil, sampled some months after application, compared with all other treatments. We show that hydrochar is less suitable for long‐term C sequestration in comparison with biochar but has potential for soil amelioration because it delivers essential nutrients. On the other hand, biochar is richer in polyaromatic C than hydrochar and therefore is more stable in the long term. We assessed biochar stability using the black carbon analysis of the different soil samples.